Hakikat Evaluasi Pendidikan Islam - Alihan Satra; Aliyah Reyhana Naveeda; Fatimah Tuzahro (Advances In Education Journal, 2025)
Islamic education aims to develop insan kamil through balanced spiritual, moral, and intellectual growth; however, this goal is often difficult to measure without proper evaluation. This study addresses the problem of how evaluation in Islamic education can be understood as a holistic and value-based assessment. The research aims to explain the essence, principles, and benefits of Islamic educational evaluation for continuous improvement. This study employs a qualitative library research method by collecting data from academic books, journals, and relevant Islamic educational literature. The findings show that Islamic education evaluation emphasizes continuity, comprehensiveness, and objectivity, covering cognitive, affective, and psychomotor domains based on Qur’anic values. Evaluation functions not only to measure learning outcomes but also to improve teaching effectiveness and character formation. In conclusion, Islamic educational evaluation has a significant impact on developing morally upright, faithful, and competent learners in accordance with Islamic principles.